Clinical significance of TM4SF1 as a tumor suppressor gene in gastric cancer - Xing‐Chun Peng; Zhi Zeng; Yu‐Ning Huang; Yun‐Chao Deng; Guo‐Hui Fu (Cancer Medicine)
Abstract Transmembrane‐4‐L‐six‐family member‐1 (TM4SF1), a tumor‐associated antigen, is overexpressed in most epithelial cell carcinomas and a potential target for antibody‐mediated therapy. However, the role of TM4SF1 in gastric cancer has not been elucidated. The aim of this study was to investigate the clinical significance of TM4SF1 expression in gastric carcinoma (GC) tissues using 152 GC tissue samples and matched adjacent nontumor tissue samples analyzed by immunohistochemistry, and 13 fresh GC tissue samples analyzed by Western blotting. The results showed that TM4SF1 was heterogeneously expressed in normal gastric mucosa, with a high expression rate in fundus mucosa. Higher levels and strong expression rate of TM4SF1 were associated with GC tissues of higher‐grade differentiation. TM4SF1 levels were lower in gastric cancer tissues than gastric noncancerous tissues. Expression of TM4SF1 was not correlated with USP10 (P = 0.157), S100A12 (P = 0.479), p53 (P = 0.249), or Ki67 (P = 0.166) in GC. The expression of TM4SF1 was significantly and negatively correlated with depth of invasion (P = 0.031), nodal metastasis (P = 0.042), TNM stage (P = 0.030), and Lauren classification (P = 0.026). There was no significant correlation between TM4SF1 expression and age, gender, tumor size, or distant metastasis (P > 0.05). The expression of TM4SF1 was associated with well overall survival (P = 0.0164). The 5‐year survival rate for patients with GC showing TM4SF1 positive was 58.82% (10/17), and the median survival time was 78 months, higher than that (12.90%, 12/93) of patients who were TM4SF1 negative, whose median survival time was 62 months. These data suggested that low expression of TM4SF1 is associated with carcinogenesis and development, tumor progression and invasion of gastric cancer, and poor overall survival of patients with GC. TM4SF1 is a tumor suppressor for GC and a novel prognostic marker for patients with GC.